Separation of three chromones from Saposhnikovia divaricata using macroporous resins followed by preparative high‐performance liquid chromatography. Issue 17 (18th July 2021) - Sun, Jiajia; Su, Xiangyi; zhang, Zhe; Hu, Dexiang; Hou, Guige; Zhao, Feng; Sun, Jufeng; Cong, Wei; Wang, Chunhua; Li, Hongjuan
Abstract: Prim‐O‐glucosylcimifugin, cimifugin, and 5‐O‐methylvisamminoside are three major chromone derivatives of Saposhnikovia divaricata that have many pharmacological activities, such as anti‐inflammatory and antitumor activities. In the present work, an effective method for the simultaneous separation of prim‐O‐glucosylcimifugin, cimifugin, and 5‐O‐methylvisamminoside with high purities was established using HPD‐300 resin coupled with preparative high‐performance liquid chromatography. The adsorption kinetics curves of the three compounds on the HPD‐300 resin were studied and found to fit well according to the pseudo‐second‐order equation. The adsorption isotherm results indicated that the adsorption process of the three compounds was exothermic. After a one‐run treatment with the resin, the contents of prim‐O‐glucosylcimifugin, cimifugin, and 5‐O‐methylvisamminoside increased from 0.29, 0.06, and 0.37% to 13.07, 2.83, and 16.91% with recovery yields of 76.38, 78.25, and 76.73%, respectively. Finally, the purities of the three compounds were found to reach more than 95% after further separation using preparative high‐performance liquid chromatography. The method developed in this study was effective and could simultaneously separate three chromones from Saposhnikovia divaricate . The experimental results also showed that the HPD‐300 resin is suitable for the separation of chromone derivatives.